Transitivity and Aspect in Sahidic Coptic Studies in the Morphosyntax of Native and Greek-Origin Verbs - Speransky, Nina (Lingua Aegyptia Studia Monographica, 2022)
Transitivity and Aspect in Sahidic Coptic consists of three studies united by the common topic of voice alternations in Sahidic. Having established that the Coptic verbal system is based on split causativity (for the term see Kulikov L.I., "Split causativity: remarks on correlations between transitivity, aspect, and tense"), the work introduces the concept of an aspect-transitivity grid, in which the unmarked infinitival form is ascribed the voice-aspect meaning according to the conjugation pattern it appears in. The work establishes a correlation between the morphosyntactic properties of verbs and their semantic properties, such as lexical aspect and agentivity. Chapter 2 explores the formal and semantic properties of the periphrastic circumstantial construction. Voice marking phenomena in Greek-origin verbs are examined in chapter 3. The results obtained in this study may be further used in language contact research, as well as in general and typological linguistics.